Pseudocapacitive Oxides and Sulfides for High-Performance Electrochemical Energy Storage - Xia, Chuan (2018)
The intermittent nature of several sustainable energy sources such as solar and wind energy has ignited the demand of electrochemical energy storage devices in the form of batteries and electrochemical capacitors. The future generation of electrochemical capacitors will in large part depend on the use of pseudocapacitive materials in one or both electrodes. Developing pseudocapacitors to have both high energy and power density is crucial for future energy storage systems. This dissertation evaluates two different material systems to achieve high energy density pseudocapacitive energy storage.